FACTORS OF JOB SATISFACTION AND THEIR EFFECTS ON EMPLOYEES’ BEHAVIOR IN A MANUFACTURING COMPANY IN THE REPUBLIC OF MACEDONIA - Ristovska Andrijana; Eftimov, Lјupcho (Faculty of Economics Pale , University of East Sarajevo, 2019)
This paper elaborates the issue about job satisfaction, observing it through the prism of the factors that lead towards its achievement, but also observing whether its absence has an impact on the employees’ behavior in the organization, employees’ productivity, absenteeism, fluctuation, as well as customers’ behavior, satisfaction and loyalty. Based on a sample of 100 employees with different gender, educational and age structure from one of the leading manufacturing companies in the Republic of Macedonia, this research revealed which factors cause job satisfaction of the employees in the Republic of Macedonia, whether the demographic characteristics influence the differences in the ranking of these factors, as well as on which conditions and processes at the workplace, the absence of job satisfaction affects significantly. We can conclude that employee job satisfaction in the country is largely determined by the factors that enable the realization of self-esteem and self-realization needs, according to the Maslow's hierarchy of needs, while the wages and the financial rewards and benefits are not ranked as the most significant factors observed at the level of all respondents. Analyzing them individually, according to gender, as well as by the level of education, which often arise as a reason for the difference in the choice of the respondents, the findings show that the financial motivators have key influence on the job satisfaction of the male employees, as well as of those with completed secondary education.
Keywords: job satisfaction, motivation, job satisfaction factors, absenteeism, fluctuation, productivity, organizational behavior.